Analysis of Health Manpower Behavior: Physicians and Dentists - Aleli D. Kraft (Philippine Institute for Development Studies (PIDS), 1995)
This study analyzes the factors affecting physician and dentist's productivity and the fees they charge for their clinic services, their willingness to participate in financing schemes and their career decisions. This paper also estimates their average consultation fees and average consultation time using three-stage least squares regression.
Keywords: 330; productivity; health sector; health manpower; consultation fee; physician/medical professions; career decision